Legal Accountability for Sustainable Development: Beyond Voluntary Commitments in Public International Law - Bunyan, Shahad; Awad, Raad; Khalifa, Attia; Mohammed, Wisam (International Journal of Law and Public Policy (IJLAPP), 2026)
Sustainable development has turned into a major normative reference point of world politics, yet, it has not been established as a legal concept since it has traditionally been a programmatic and voluntary concept. Although broad support is achieved by the use of various tools like Rio Declaration and Sustainable Development Goals, the measures of legal accountability are ad hoc and uneven. The article is a response to the doctrinal issue of how international environmental law and international human rights law can turn sustainable development into a precept into a legal system of accountability. It finds a structural disjuncture between normative proliferation and juridical enforceability, that sustainable development has been hampered by the pre-eminence of soft-law, feeble institutionalization and the inadequate articulation of adjudicative processes. The article analyses through a doctrinal legal approach the development of due diligence, extraterritorial human rights duties, climate litigation, and new doctrines of state and corporate responsibility. It shows that there is a growing interpretation of sustainability by courts and treaty bodies which have binding obligations in relation to prevention, precaution, intergenerational equity and the protection of rights. The article suggests that sustainable development is experiencing a process of normative hardening, in which the practices of judicial reasoning and accountability transform political commitments into enforceable obligations. The paper concludes that sustainable development could be used as a legally binding construct when integrated with standards of due diligence, rights-based policies, and responsibility dogmas, and no longer be a voluntary construct, but a structured responsibility. This reconceptualization adds to the scholarship by explaining the doctrinal avenues where sustainability obtains enforceable legal nature.